PENGARUH HARGA DAN LOKASI TERHADAP MINAT BELI PRODUK SELASAR SPACE CAFE BALARAJA - Riyan Kurniawan; I Gusti Kade Birawan; Mudhita Elviani (Jurnal Penelitian Multidisiplin Ilmu, 2022)
Abstract Research with the title The Effect of Price and Location on Purchase Internet of Selasar Space Cafe Balaraja Products to find out hou much influence the independent variabel hace on the dependent variable. This reserach was held in the lobby cafe, Balaraja, tangerang Regency, Banten. The sampling collecting data using a questionnaire with 96 respondents. The research method used in this study is quantitative where in this study there are 3 variables represented by the independent variables, namely Price (X1), Location (X2) and the dependent variable, namely Product Purchase Interest (Y).The result of data analysis statistically prove that the price and location variables have a positif and significant effect on buying interest simultaneously as shown by the acquisition os the value of the termibation cosfficient of 0,653% which means that buying interest is 65,3%, meaning simultaneous, the magnitude of the influence of price and location simultaneously. Simultaneous buying interest can be explained by 65.30% and the remaining 34.7% is influnced by other factor not included in this study.